Implementation and evaluation of a palliative care training unit for EMS providers - Hauch, Holger; El Mohaui, Naual; Sander, Michael; Rellensmann, Georg; Berthold, Daniel; Kriwy, Peter; Zernikow, Boris; Wager, Julia; Schneck, Emmanuel (Frontiers in Pediatrics, 2023)
Background The prevalence of children with life-limiting conditions (LLCs) is rising. It is characteristic for these children to require 24/7 care. In emergencies, families must decide to call the emergency medical service (EMS) or a palliative care team (PCT)—if available. For EMS teams, an emergency in a child with an LLC is a rare event. Therefore, EMS providers asked for a training unit (TU) to improve their knowledge and skills in pediatric palliative care. Aim of the study The questions were as follows: whether a TU is feasible, whether its integration into the EMS training program was accepted, and whether an improvement of knowledge can be achieved. Methods We designed and implemented a brief TU based on findings of a previous study that included 1,005 EMS providers. The topics covered were: (1) basics in palliative home care, (2) theoretical aspects, and (3) practical aspects. After participating in the TU, the participants were given a questionnaire to re-evaluate their learning gains and self-confidence in dealing with emergencies in pediatric patients with LLC. Results 782 (77.8%) of 1,005 participants of the previous study responded to the questionnaire. The average age was 34.9 years (±10.7 years SD), and 75.3% were male. The average work experience was 11.4 years (±9.5 years SD), and 15.2% were medical doctors. We found an increase in theoretical knowledge and enhanced self-confidence in dealing with emergencies in patients with LLC (confidence: before training: 3.3 ± 2.0 SD; after training: 5.7 ± 2.1 SD; min.: 1; max.: 10; p < 0.001). The participants changed their approaches to a fictitious case report from more invasive to less invasive treatment. Most participants wanted to communicate directly with PCTs and demanded a standard operating procedure (SOP) for treating patients with LLC. We discussed a proposal for an SOP with the participants. Conclusion EMS providers want to be prepared for emergencies in children with LLCs. A brief TU can improve their knowledge and confidence to handle these situations adequately. This TU is the first step to improve collaboration between PCTs and EMS teams.